Student Engagement in Improving Access to Taught Course Content at LSE Library: practicalities and Pitfalls. Issue 2 (1st October 2020) - Marks, Nadia
Abstract: As in other academic libraries, LSE (London School of Economics and Political Science) Library does not meet student expectations for access to core readings despite increasing provision. We used user experience research to gather evidence of student experience, behaviours, and preferences for taught course content with the aim of making improvements. We found that convenience is the deciding factor for students in choosing what and how to read due the necessity of keeping up with weekly reading. They prefer PDF journal articles due to their structure and functionality and dislike e-books. This suggests that for book chapters we should offer accessible scans where possible while advocating for improved e-book functionality and licencing. Our research underlines the role of liaison librarians in encouraging appropriate use of reading lists so that they scaffold rather than spoon-feed, as students appreciate well-structured and signposted reading lists, but approach their reading instrumentally. Our next step is to engage with teaching staff.